Western Centric Medicine for Covid-19 and Its Contradictions: Can African Alternate Solutions Be the Cure? - Adunimay, Anslem Wongibeh; Ojo, Tinuade A. (Frontiers in Political Science, 2022)
The full impact of COVID-19 is yet to be fully understood, and while there are many unknowns, the rapid and continued reliance on the social media cannot be denied. Some Global Economy and World Health Organisations have discouraged the usage of traditional medicine for COVID-19 treatment. However, some African states such as Tanzania, Equatorial Guinea, Guinea-Bissau, Guinea Conakry, and Togo have engaged with formal researchers to see if traditional medicine can treat COVID-19. Nevertheless, there is still a lot of hesitancy amongst African populations in getting vaccinated. The paper conceptualises the criticism of Western-centric medicine and investigates the promotion of alternate approaches in the African economy. The article situates the study context by exploring the African economy's socio-politics and public health governance. It investigates explicitly African states responses to conventional treatment by analysing the role of traditional medicine and its efficacy as well as the possible effects on the continent. The methodological framework engaged a review approach relying heavily on reputable secondary sources from government publications, journal articles, books and publications from professional bodies and institutional search engines. The data was analysed in themes supporting the study aim's and objectives. The paper concludes that Africa could consolidate the readily available knowledge and give opportunities to traditional medical therapies that are cheap, convenient and safe for public health, especially for COVID-19 supposedly cure.